India's role in facilitating trade under SAFTA - Nisha Taneja; Shravani Prakash; Pallavi Kalita (Indian Council for Research on International Economic Relations (ICRIER), 2013)
Economic integration in South Asia is governed by India's relations with the other economies of the region and it is also at the helm of all trade facilitation and transit issues of the region. Concessions given by India under SAFTA for LDCs have greatly benefitted Bangladesh and concessions to non-LDC members have applied to its imports from Pakistan. India has given significant concessions to Sri Lanka and Nepal under bilateral trade agreements. In a major breakthrough, Pakistan has granted the Most Favoured Nation status to India in 2011, thereby giving a fresh impetus to the SAFTA process. In this changed scenario, further efforts by India would benefit the regional trade integration process much more than before. This paper examines the ground covered so far by India and the challenges that remain for it to realize the benefits under SAFTA. A number of issues that have already been addressed but need to be dealt with further, including liberalisation of tariffs (including trimming sensitive lists), non tariff barriers, transport and transit barriers and customs reforms.
Keywords: F10; F15; R40; F53; F50; 330; Asia/ SAFTA; trade facilitation; bilateral FTAs; India; non-tariff barriers; tariff liberalization; Handelsliberalisierung; Zollpolitik; Indien; Nichttarifäre Handelshemmnisse; Südasien